2010
DOI: 10.1159/000272060
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Cadmium Chloride Induced Molecular and Functional Alterations in Airway Epithelial Cells

Abstract: Epidemiological studies show that cadmium (Cd) exposure causes pulmonary damage, such as emphysema, pneumonitis, and lung cancer. However, the mechanisms leading to pulmonary toxicity are not yet fully elucidated. The aim of this study was to further investigate cadmium chloride (CdCl2) induced toxicity using Calu-3 cells as an in vitro model of human bronchial epithelial cells. CdCl2 induced effects following either apical or basolateral exposure were evaluated by Neutral Red Uptake (NRU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 54 publications
1
21
0
1
Order By: Relevance
“…MT expression is frequently observed in lung carcinoma tissue samples from human patients (Eckschlager et al, 2009). It has previously been shown that epithelial barrier disruption following low-dose exposure to cadmium in airway epithelia results in elevated MT expression (Forti et al, 2010). Elevated MT levels are observed in the present study in CCT-LC cells when they acquired cancer cell characteristics with chronic cadmium exposure, supporting the association between MT and malignant lung phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…MT expression is frequently observed in lung carcinoma tissue samples from human patients (Eckschlager et al, 2009). It has previously been shown that epithelial barrier disruption following low-dose exposure to cadmium in airway epithelia results in elevated MT expression (Forti et al, 2010). Elevated MT levels are observed in the present study in CCT-LC cells when they acquired cancer cell characteristics with chronic cadmium exposure, supporting the association between MT and malignant lung phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…While 16HBE 14o-cells have been reported to exhibit morphological features including apical microvilli and cilia (Cozens et al, 1994), in our experience cilia are absent from polarized 16HBE 14o-cultures. In addition to their use for toxicology (Forti et al, 2010(Forti et al, , 2011 and drug transport studies, 16HBE 14o-and Calu-3 cell lines are frequently used for analysis of pathways involved in barrier function in response to environmental agents including allergens (Vinhas et al, 2011;Wan et al, 2001), particulates (Banga et al, 2012), cigarette smoke (Heijink et al, 2012) or viral infections (Harcourt et al, 2011;Rezaee et al, 2011). The other frequently used bronchial epithelial cell line, BEAS2B (Reddel et al, 1988), is not of value for transport studies as it fails to form an appreciable barrier (Forbes and Ehrhardt, 2005).…”
Section: Cfdeo-/6rep-cftrmentioning
confidence: 99%
“…Хоча активація лейкоцитів відіграє важливу роль у хворобах органів дихання під час надходження Кадмію, цей елемент і безпосередньо впливає на клітини епі-телію альвеол і бронхів, стимулюючи утворення в них активних форм Оксигену, по-рушення бар'єрної функції та загибель за участю апоптозу [30,68]. У дослідженнях in vitro показано, що після культивування зрізів легень упродовж 7 діб за наявності в середовищі 5,0 і 10,0 мкмоль CdCl 2 рівень виживання клітин становить, відповід-но, 40 і 6% [57].…”
Section: CDunclassified